The BFG - Dahl, Roald (Puffin Books London, 1992)
Kidsnatched from her orphanage by a BFG (Big Friendly Giant), who spends his life blowing happy dreams to children, Sophie concocts with him a plan to save the world from nine other man-gobbling cannybull giants